Model Pembelajaran Cooperative Integrated Reading and Composition based on Flipped Classroom Learning (CIRC-b-FCL) - Jufrizal, Jufrizal; Harida, Eka Sustri; Syarif, Hermawati; Ratmanida, Ratmanida; Lubis, Rayendriani Fahmei (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2021)
This study aims to determine the students’ attitude in learning reading comprehension at English Program IAIN Padangsidimpuan by using CIRC-b-FCL model. The research was done by using quantitative study by using questionnaires as the instrument. The data were analysed statistically. The students’ attitude was seen from the students’ cognitive, affective, and psycho-motoric result (Ahmadi, 2007). By the result, it was seen that the students’ attitude is better by using this model, it was seen by the result of cognitive (81.83) and psychomotor  (82) are very good, and the effective attitude (77.08) was good. So, it can be concluded that the CIRC-b-FCL can be used for the students’ attitude in learning reading comprehension.